Living life: overlooked aspects of urban employment - Garrett, James L. (International Food Policy Research Institute, 2004)
With urban dwellers purchasing 80 percent or more of their food, understanding urban employment is critical to designing policies and programs to address urban hunger and poverty. Reviewing the literature, but also using data from household surveys conducted by the International Food Policy Research Institute (IFPRI) and others in five countries of Latin America, Asia, and Africa, this paper profiles urban employment in developing-country cities. It highlights some often-overlooked aspects of urban conditions, most especially the importance of agriculture, the continuing importance of the formal sector, and seasonality of income, even among those not connected to agriculture. It also examines the connections between poverty and employment; looks at where people work and what they do; and highlights the importance of personal networks, the informal sector, and the concerns of women. Finally, it notes some dynamic forces shaping the future of urban employment and suggests some guidelines for policies and programs.